Midnight flyboys : the American bomber crews and Allied secret agents who aided the French Resistance in World War II - Henderson, Bruce, 1946- (Gallery Books, 2025)
"In 1943, the OSS -- precursor to the CIA -- came up with a plan to increase its support to the French resistance forces that were fighting the Nazis. To start, the OSS recruited some of the best American bomber pilots and crews to a secret airfield twenty miles west of London and briefed them on the intended mission. Given a choice to stay or leave, every airman volunteered for what became known as Operation Carpetbagger. Their dangerous plan called for a new kind of flying: taking their B-24 Liberator bombers in the middle of the night across the English Channel and down to extremely low altitudes in Nazi-occupied France to find drop zones in dark fields. On the ground, resistance members waited to receive steel containers filled with everything from rifles and hand grenades to medicine and bicycle tires. Some nights, the flyers also dropped Allied secret agents by parachute to assist the French partisans. Though their story remained classified for more than fifty years, the Carpetbaggers ultimately received a Presidential Unit Citation from the US military, which declared: "it is safe to say that no group of this size has made a greater contribution to the war effort." Along with other members of the wartime OSS, they were also awarded the Congressional Gold Medal. Based on exclusive research and interviews, the definitive story of these heroic flyers -- and of the brave secret agents and resistance leaders they aided-- -- can now be told." --